COMPARISON OF STRESS AND ANXIETY LEVELS OF THE KOSOVAR POPULATION WITH DEMOGRAPHIC VARIABLES DURING THE COVID-19 PANDEMIC - Delvina Beka; Valbona Uka; Zana Qehaja (Galaxy International Interdisciplinary Research Journal, 2021)
The pandemic of COVID-19 has had a major impact on public mental health. As a result, in times of crisis, such as a pandemic, monitoring and oversight of the population’s mental health is a top priority.